Mapping interactional organisation in CLIL classrooms: Saudi tertiary level - Jawhar, Sabria S.; Alnofaie, Haifa (Advances in Social Sciences Research Journal, 2016)
This article uses a conversation analysis (CA) methodology to investigate classroom interaction in Content and Language Integrated Learning (CLIL) classrooms in Saudi higher education. Most of the work that has examined classroom interaction in CLIL has used various frameworks, such as an interactional framework and/ or a discourse-pragmatic framework. There is still lack of research that explores the micro details of talk-in-interaction in CLIL contexts using CA, particularly in higher education. Based on a corpus of 16 tertiary education CLIL lessons, this article provides an account of the interactional organisation of Saudi higher education CLIL classrooms. It also provides an in-depth investigation of the ways in which Saudi students display orientation to knowledge within this instructional setting.